Model and Activity Development in Adult Health Promotion Foundation, the Adult Health Learning Center, Wat Santiwiwek Takian Sub – District, Kabcherng District, Surin Province - et. al., Phramaha Wisit Dhirawangso (Kleebmuang), (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objectives of this research were: 1) to study the requirements and taking care of adult health in the adult health, learning center of Wat Santiwiwek, Takian sub-district, Kabcherng district, Surin Province; 2) to develop models and activities in the adult health promotion foundation; and 3) to analyze the means in the adult health promotion foundation in the adult health learning center of Wat Santiwiwek, Takian sub-district, Kabcherng district, Surin Province. This work is qualitative research. Document studying, in-depth interviews, and a focus group with 20 key persons were used. The Data was analyzed by content analysis and analytic induction. Results indicated that 1) The needs and health care of the elderly health learning center of Wat Santiwiwek, Takian sub-district, Kabcherng district, Surin province had found that the elderly need to be healthy and free from diseases. They should have a healthy diet and need to have recreational activities. 2) the development of model and activity in the adult health promotion foundation had found that there are three forms and activities for enhancing the well-being of the elderly: (1) physical well-being, (2) mental and intellectual well-being, and (3) social well-being. 3) Guidelines for enhancing well-being had found that: - 1) physical aspects include encouraging the elderly to understand the health, 2) psychological and intellectual aspects, including encouraging the elderly to participate in activities with others, and 3) social aspects, i.e., encourage activities with their families. The community should encourage the elderly to attend merit-making temples for achieving peace of mind.